Functionalized 12 µm Polyethylene Separator to Realize Dendrite‐Free Lithium Deposition toward Highly Stable Lithium‐Metal Batteries. Issue 13 (7th March 2022) - Zhao, Qiannan; Wang, Ronghua; Hu, Xiaolin; Wang, Yumei; Lu, Guanjie; Yang, Zuguang; Liu, Qiwen; Yang, Xiukang; Pan, Fusheng; Xu, Chaohe
Abstract: Direct application of metallic lithium (Li) as the anode in rechargeable lithium metal batteries (LMBs) is still hindered by some annoying issues such as lithium dendrites formation, low Coulombic efficiency, and safety concerns arising therefrom. Herein, an advanced composite separator is prepared by facilely blade coating lightweight and thin functional layers on commercial 12 µm polyethylene separator to stabilize the Li anode. The composite separator simultaneously improves the Li ion transport and lithium deposition behaviors with uniform lithium ion distribution properties, enabling the dendrite‐free Li deposition. As a result, the lithium anode can stably cycle up to 3000 cycles with the high capacity of 3.5 mAh cm −2 . Moreover, the composite separator exhibits wide compatibility in LMBs (Li–S and Li‐ion battery) and delivers stable cycling performance and high Coulombic efficiency both in coin and lab‐level soft‐pack cells. Thus, this cost‐effective modification strategy exhibits great application potential in high‐energy LMBs. Abstract : The designed functionalized layer can regulate lithium (Li) ions distribution and ensure uniform Li ions flux and deposition even in the presence of rough defects or cracks disturbance. Therefore, ultralong cycling dendrite‐free Li anodes can be achieved with this special designed TV‐PE separator, endowing great potential in the practical application of future high energy lithium metal batteries.